Multilayer film, method of manufacturing the same, metal-clad laminate, and method of manufacturing a printed circuit board
Patent Information
- Application Number
- KR1020227024870
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-26
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-03-26
Smart Images

Figure 112022074632819-PCT00001 
Figure 112022074632819-PCT00002
Abstract
Description
Technology Field
[0001] The present invention relates to a multilayer film having a predetermined base film layer and a predetermined buffer layer formed on both sides of the base film layer, a method for manufacturing the same, a metal-clad laminate, and a method for manufacturing a printed circuit board. Background Technology
[0002] A multilayer film having a polyimide as a base film layer and layers containing a tetrafluoroethylene-based polymer on both sides thereof is known as a material for electronic components such as coverlays, flexible flat cables, and printed circuit boards. In such a multilayer film, an embodiment has been proposed in which a polyimide having a low absorption rate and a low glass transition point and a tetrafluoroethylene-based polymer having a low melting temperature are used (Patent Document 1). Prior art literature
[0003] Japanese Published Patent Application No. 2015-176921 The problem to be solved
[0004] These multilayer films have excellent moisture resistance and interlayer adhesion, but they have a problem with high-temperature heat resistance. Therefore, when these multilayer films are provided to processing processes exposed to high temperatures, for example, when the multilayer film and metal foil are high-temperature compressed to form a metal-clad laminate, or when a transmission circuit is formed on the metal foil of the metal-clad laminate and provided to a soldering process at 288°C or higher to form a printed circuit board, wrinkles or swelling occur in the multilayer film, and the production efficiency is likely to decrease.
[0005] The inventors have discovered that by arranging layers containing a tetrafluoroethylene-based polymer having a melting temperature above a predetermined temperature on both sides of a layer containing a polyimide having a glass transition point below a predetermined temperature, a multilayer film that is resistant to thermal stretching and has heat resistance to higher temperatures is obtained. Such a multilayer film is optimal for high-temperature processing processes, such as processing into a printed circuit board.
[0006] The present invention aims to provide a multilayer film having the above physical properties, a method for manufacturing the same, a metal-clad laminate obtained therefrom, and a method for manufacturing a printed circuit board that processes the same. means of solving the problem
[0007] The present invention has the following aspects.
[0008] <1> A multilayer film comprising a base film layer containing a polyimide having a glass transition point of less than 288°C, and a buffer layer formed on both sides of the base film layer, comprising a tetrafluoroethylene-based polymer having a melting temperature of 288°C or higher and containing a unit based on perfluoro(alkyl vinyl ether).
[0009] <2> The above base film layer and each of the above buffer layers are in direct contact, <1> multilayer film of.
[0010] <3> The thickness of the above multilayer film is 50 μm or more, <1> or <2> Multilayer film as described in
[0011] <4> The thickness of the base film layer is 50 μm or less, and the thickness of each of the buffer layers is 5 μm or more, <1> ~ <3> One of the multilayer films.
[0012] <5> The ratio of the total thickness of the buffer layer to the thickness of the base film layer is 0.8 or greater, <1> ~ <4> One of the multilayer films.
[0013] <6> The tensile modulus of the above base film layer at 320 ℃ is 0.2 GPa or higher, <1> ~ <5> One of the multilayer films.
[0014] <7> The above tetrafluoroethylene-based polymer is a polymer comprising a perfluoro(alkyl vinyl ether)-based unit and having polar functional groups, or a polymer comprising 2.0 to 5.0 mol% of the perfluoro(alkyl vinyl ether)-based unit with respect to the total units and not having polar functional groups. <1> ~ <6> One of the multilayer films.
[0015] <8> The above buffer layer further comprises an aromatic polymer, <1> ~ <7> One of the multilayer films.
[0016] <9> The thermal expansion rate of the above multilayer film, measured by heating at 150°C for 30 minutes, is -2 to +1%, <1> ~ <8> One of the multilayer films.
[0017] <10> <1> ~ <9> A method for manufacturing a multilayer film as described in any one of the above, wherein each of the buffer layers is formed from a liquid composition comprising a powder of the tetrafluoroethylene-based polymer.
[0018] <11> <1> ~ <9> A method for manufacturing any one of the multilayer films, wherein each of the buffer layers is formed from a film comprising the tetrafluoroethylene-based polymer.
[0019] <12> A metal-coated laminate having a base film layer comprising a polyimide having a glass transition point of less than 288°C, a buffer layer formed on both sides of the base film layer comprising a tetrafluoroethylene-based polymer having a melting point of 288°C or higher and containing a unit based on perfluoro(alkyl vinyl ether), and a metal foil layer formed on the side of at least one of the buffer layers opposite to the base film layer.
[0020] <13> printed wiring board material, <12> Metal clad laminate.
[0021] <14> solder with a heat resistance temperature of 288 ℃ or higher, <12> or <13> Metal-clad laminate as described in
[0022] <15> <12> ~ <14> A method for manufacturing a printed circuit board, wherein the metal foil layer of any one of the metal-clad laminates is processed by etching to form a transmission circuit, thereby obtaining a printed circuit board. Effects of the invention
[0023] According to the present invention, a multilayer film having a base film layer comprising a predetermined polyimide and a buffer layer formed on both sides of the base film layer and comprising a predetermined tetrafluoroethylene-based polymer, a metal-clad laminate, and a printed circuit board are obtained. Specific details for implementing the invention
[0024] The following terms have the following meanings.
[0025] "Average particle size (D50)" is the cumulative 50% diameter based on the volume of the object (powder and filler) obtained by the laser diffraction and scattering method. That is, the particle size distribution of the object is measured by the laser diffraction and scattering method, and a cumulative curve is obtained by setting the total volume of the particle group of the object to 100%, and it is the particle size at the point where the cumulative volume becomes 50% on the cumulative curve.
[0026] "D90" is the cumulative diameter of the object based on its volume, measured in the same way.
[0027] "Melting temperature (melting point)" is the temperature corresponding to the maximum value of the melting peak of the polymer measured by differential scanning calorimetry (DSC).
[0028] "Glass transition point (Tg)" is a value measured by analyzing the polymer using dynamic viscoelasticity measurement (DMA).
[0029] "Viscosity" is a value obtained by measuring the liquid composition using a Type B viscometer under conditions of 25°C and a rotation speed of 30 rpm. The measurement is repeated three times, and the average of the three measurements is used.
[0030] "Thixobi" is a value calculated by dividing the viscosity obtained by measuring a liquid composition at a rotational speed of 30 rpm by the viscosity obtained by measuring at a rotational speed of 60 rpm.
[0031] "Tensile modulus" is a value measured by analyzing a film at a measurement frequency of 10 Hz using a wide-range viscoelastic measuring device.
[0032] In the polymer, the “unit” may be an atomic group directly formed from one molecule of monomer by polymerization, or an atomic group in which a part of the structure of the atomic group formed from one molecule of monomer is transformed by treating the obtained polymer by a predetermined method. A unit based on monomer A included in the polymer is also simply referred to as a “monomer A unit.”
[0033] "10-point average illuminance" is a value specified by measuring the film in accordance with Annex JA of JIS B 0601:2013.
[0034] The multilayer film of the present invention comprises a base film layer and a buffer layer formed on both sides of the base film layer. The base film layer comprises a polyimide having a glass transition point of less than 288°C (hereinafter also referred to as "PI"), and the buffer layer comprises a tetrafluoroethylene-based polymer having a melting temperature of 288°C or higher and a unit based on perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE unit").
[0035] The multilayer film of the present invention possesses high-temperature heat resistance and low thermal elasticity in addition to excellent interlayer adhesion and moisture resistance. Although the reason for this is not necessarily clear, it is thought to be as follows.
[0036] PI, which has a low glass transition point, has excellent moisture resistance and flexibility, but is prone to softening at high temperatures. In addition, tetrafluoroethylene-based polymers generally have a high coefficient of linear expansion, so they tend to shrink when cooled from a high temperature state. For this reason, it was thought that in multilayer films combining layers containing such polymers, the layer containing PI deforms when the temperature rises under exposure to high temperatures, and the layer containing the tetrafluoroethylene-based polymer shrinks when the temperature drops after exposure to high temperatures, making it prone to wrinkling or swelling. However, the inventors have discovered that a layer containing a tetrafluoroethylene-based polymer (F polymer) containing PAVE units functions as a thermal buffer layer due to its heat resistance, thereby suppressing the deformation of the layer containing PI, and that its shrinkage is buffered due to its melt flowability.
[0037] As a result, the multilayer film of the present invention is equipped with high temperature heat resistance and low thermal elasticity in addition to excellent interlayer adhesion and moisture resistance, and is thought to be preferably used as a material for applications requiring a high-temperature process for processing printed circuit boards, etc.
[0038] The F polymer in the present invention is a polymer comprising tetrafluoroethylene (TFE)-based units (TFE units) and PAVE units.
[0039] The F polymer may additionally have units based on other comonomers.
[0040] As for PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 and CF2=CFOCF2CF2CF3(PPVE) are preferred, and PPVE is more preferred.
[0041] The melting temperature of the F polymer is 288°C or higher, and preferably 300°C or higher. The melting temperature of the F polymer is preferably 350°C or lower, and more preferably 320°C or lower. In this case, the heat resistance of the multilayer film is more likely to be superior, and it is less likely to be thermally stretched.
[0042] The glass transition point of the F polymer is preferably 75 to 125 ℃, and more preferably 80 to 100 ℃.
[0043] It is preferable that the F polymer has a polar functional group (an oxygen-containing polar group). The polar functional group may be included in the unit of the F polymer or may be included in the terminal group of the main chain of the F polymer. Examples of the latter embodiment include an F polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having a polar functional group obtained by plasma treatment or ionization treatment of the F polymer.
[0044] As for polar functional groups, hydroxyl groups and carbonyl groups are preferred, and carbonyl groups are more preferred from the perspective of increasing adhesion to the buffer layer.
[0045] As for the hydroxyl group containing group, a group containing an alcoholic hydroxyl group is preferred, and -CF2CH2OH and -C(CF3)2OH are more preferred.
[0046] The carbonyl group containing the carbonyl group is a group containing a carbonyl group (>C(O)), and the carbonyl group containing the carbonyl group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), and a carbonate group (-OC(O)O-), and the acid anhydride residue is more preferred.
[0047] When the F polymer has carbonyl groups, the number of carbonyl groups in the F polymer is 1 × 10⁻¹⁰, the number of carbon atoms in the main chain. 6For each, 100 to 5000 are preferred, 300 to 3000 are more preferred, and 800 to 1500 are even more preferred. In addition, the number of carbonyl group-containing groups in the F polymer can be quantified by the composition of the polymer or by the method described in International Publication No. 2020 / 145133.
[0048] As for the F polymer, additionally, a polymer (1) having polar functional groups, comprising a unit based on a monomer having polar functional groups, and a polymer (2) having 2.0 to 5.0 mol% of PAVE units with respect to the total unit and not having polar functional groups are preferred, and polymer (1) is more preferred.
[0049] These F polymers are prone to forming small spheres. Buffer layers containing such F polymers tend to have excellent surface smoothness, and as the buffer layer and the base polymer layer adhere closely, the multilayer film tends to have excellent peel strength and water resistance.
[0050] It is preferable that the polymer (1) contains, with respect to the total unit, 90 to 99 mol% of TFE units, 0.5 to 9.97 mol% of PAVE units, and 0.01 to 3 mol% of units based on monomers having polar functional groups.
[0051] In addition, as monomers having polar functional groups, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic acid anhydride (alias: hymic anhydride; hereinafter also referred to as "NAH") are preferred.
[0052] Specific examples of polymers (1) include the polymer described in International Publication No. 2018 / 16644.
[0053] The polymer (2) is composed only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol% of TFE units and 2.0 to 5.0 mol% of PAVE units with respect to the total units.
[0054] The content of PAVE units in the polymer (2) is preferably 2.1 to 5.0 mol% with respect to the total unit, and more preferably 2.2 to 5.0 mol%.
[0055] In addition, the polymer (2) does not have polar functional groups, which is 1 × 10 of the number of carbon atoms constituting the polymer main chain. 6 This means that the number of polar functional groups in the polymer is less than 500. The number of polar functional groups is preferably 100 or less, and more preferably less than 50. The lower limit of the number of polar functional groups is typically 0.
[0056] The polymer (2) may be manufactured using a polymerization initiator or a chain transfer agent that does not generate a polar functional group as a terminal group of the polymer chain, or may be manufactured by fluorination of an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from the polymerization initiator at the terminal of the main chain of the polymer). As a method of fluorination treatment, a method using fluorine gas may be used (see Japanese Patent Publication No. 2019-194314, etc.).
[0057] In the buffer layer of the present invention, the content of F polymer is preferably 50 mass% or more, and more preferably 60 mass% or more. The upper limit of the content of F polymer is 100 mass%.
[0058] The buffer layer may additionally include another resin (polymer). The other resin may be a thermosetting resin or a thermoplastic resin.
[0059] The other resin is preferably an aromatic polymer. In this case, the buffer layer has excellent UV absorption, and the multilayer film is likely to have excellent UV processability.
[0060] Other resins include epoxy resin, maleimide resin, urethane resin, polyimide, polyamic acid, polyamideimide, polyphenylene ether, polyphenylene oxide, liquid crystal polyester, and fluoropolymers other than F polymer.
[0061] Other resins preferred include maleimide resin, polyimide, and polyamic acid. When at least one of these resins is included, the multilayer film is likely to have excellent flexibility and peel strength. Other resins preferred include maleimide resin, polyimide, and polyamic acid, all of which are aromatic.
[0062] It is preferable that the polyimide be thermoplastic.
[0063] In this case, the total content of maleimide, polyimide, and polyamic acid in the buffer layer is preferably 0.1 to 30 mass%, and more preferably 1 to 10 mass%. The ratio of the total content of maleimide, polyimide, and polyamic acid to the content of F polymer is preferably 1.0 or less, and more preferably 0.01 to 0.5.
[0064] As for other resins, fluoropolymers other than F polymers are also preferred, and non-thermo-meltable PTFE is more preferred. In this case, in a multilayer film, properties based on PTFE (electrical properties such as low dielectric loss tangent) are likely to be significantly exhibited.
[0065] In this case, the content of non-thermo-meltable PTFE is preferably 1 to 30 mass%, and more preferably 5 to 20 mass%. The ratio (mass ratio) of the content of non-thermo-meltable PTFE to the content of F polymer is preferably 1.0 or less, and more preferably 0.1 to 0.4.
[0066] It is preferable that the buffer layer additionally include an inorganic filler to further improve the low linear expansion and electrical properties of the multilayer film.
[0067] As for inorganic fillers, nitride fillers and inorganic oxide fillers are preferred, boron nitride fillers, beryllia fillers (fillers of beryllium oxide), silicate fillers (silica fillers, wollastonite fillers, talc fillers), and metal oxide fillers (cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, etc.) are more preferred, and silica fillers are even more preferred.
[0068] The silica content in the inorganic filler is preferably 50 mass% or more, and more preferably 75 mass% or more. The upper limit of the silica content is 100 mass%.
[0069] It is preferable that at least a portion of the surface of the inorganic filler be surface-treated. Examples of surface treatment agents used for such surface treatment include polyhydric alcohols (trimethylolethane, pentaerythritol, propylene glycol, etc.), saturated fatty acids (stearic acid, lauric acid, etc.), their esters, alkanolamines, amines (trimethylamine, triethylamine, etc.), paraffin waxes, silane coupling agents, silicones, and polysiloxanes.
[0070] As silane coupling agents, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-isocyanatepropyltriethoxysilane are preferred.
[0071] The average particle size of the inorganic filler is preferably 20 μm or less, and more preferably 10 μm or less. The average particle size is preferably 0.1 μm or more, and more preferably 1 μm or more.
[0072] The shape of the inorganic filler may be granular, needle-shaped (fibrous), or plate-shaped. Specific shapes of the inorganic filler include spherical, flaky, lamellar, leaf-shaped, apricot-shaped, columnar, crown-shaped, isometric, leaf-shaped, mica-shaped, block-shaped, flat, wedge-shaped, rosette-shaped, reticulate, and prismatic shapes.
[0073] Specific examples of inorganic fillers include silica fillers (e.g., the "Adoma Fine" series manufactured by Adomatex), zinc oxide surface-treated with esters such as propylene glycol dicaprate (e.g., the "FINEX" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica (e.g., the "SFP" series manufactured by Denka), polyhydric alcohols coated with inorganic materials (e.g., the "Taipeike" series manufactured by Ishihara Sangyo), rutile-type titanium oxide surface-treated with alkylsilane (e.g., the "JMT" series manufactured by Teika), hollow silica fillers (e.g., the "E-SPHERES" series manufactured by Taiheiyo Cement Co., Ltd., the "Sirinax" series manufactured by Nittetsu Mining Co., Ltd., the "Ecocosphere" series manufactured by Emerson & Cumming Co., Ltd.), talc fillers (e.g., the "SG" series manufactured by Nippon Talc), steatite fillers (e.g., the "BST" series manufactured by Nippon Talc), and boron nitride fillers. Examples include the “UHP” series manufactured by Showa Electric Company, and the “Denka Boron Nitride” series manufactured by Denka Company (“GP”, “HGP” grades), etc.
[0074] The content of the inorganic filler in the buffer layer is preferably 1 mass% or more, and more preferably 3 mass% or more. The content of the inorganic filler is preferably 40 mass% or less, more preferably 30 mass% or less, and more preferably 20 mass% or less.
[0075] The ratio (mass ratio) of the content of inorganic filler to the content of F polymer in the buffer layer is preferably 0.01 or higher, and more preferably 0.1 or higher. The ratio is preferably 1 or lower, and more preferably 0.8 or lower.
[0076] In addition to the components described above, the buffer layer may also include additives such as silane coupling agents, dehydrating agents, plasticizers, weathering agents, antioxidants, heat stabilizers, lubricants, antistatic agents, whitening agents, coloring agents, conductive agents, release agents, surface treatment agents, and flame retardants.
[0077] In the present invention, the glass transition point of PI is less than 288°C, more preferably less than 275°C, and even more preferably 260°C or lower. The glass transition point of PI is preferably 200°C or higher.
[0078] It is preferable to obtain PI from a polyamic acid obtained by polymerizing an aromatic diamine component and a tetracarboxylic acid component.
[0079] Examples of aromatic diamine components include paraphenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, and 2,2'-bis(4-aminophenoxyphenyl)propane. Two or more types of aromatic diamine components may be used.
[0080] Examples of tetracarboxylic acid components include pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, oxydiphthalic acid, 2,3',3,4'-biphenyltetracarboxylic acid, and 3,3',4,4'-benzophenonetetracarboxylic acid, and preferably, pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, oxydiphthalic acid, and the dihydrogenates of these tetracarboxylic acids may be used. Two or more types of tetracarboxylic acid components may be used.
[0081] The base film layer in the present invention may be obtained by a method of casting a solution containing polyamic acid obtained by polymerizing the aromatic diamine described above and the tetracarboxylic acid component described above into a film and thermally decyclizing and desolvating it, or by mixing a cyclization catalyst and a dehydrating agent into a polyamic acid solution, chemically decyclating it to produce a gel film, and then heating and desolvating it. The solution containing polyamic acid may additionally include a cyclization catalyst (imidization catalyst), a dehydrating agent, and a gelation retardant.
[0082] Specific examples of the base film layer include “Kapton 50EN-S” (manufactured by Toray DuPont Corp.), “Kapton 100EN” (manufactured by Toray DuPont Corp.), “Kapton 100H” (manufactured by Toray DuPont Corp.), “Kapton 100KJ” (manufactured by DuPont), “Kapton 100JP” (manufactured by DuPont USA), and “Kapton 100LK” (manufactured by Toray DuPont Corp.).
[0083] The base film layer may additionally include plasticizers, other resins, colorants, various additives, etc. Examples of additives include antistatic agents, flame retardants, heat stabilizers, UV absorbers, lubricants, release agents, crystallization nucleating agents, and reinforcing agents (fillers).
[0084] The tensile modulus of the base film layer at 320°C is preferably 0.2 GPa or higher, and more preferably 0.4 GPa or higher. The tensile modulus is preferably 10 GPa or lower, and more preferably 5 GPa or lower.
[0085] In this case, when processing the multilayer film, it is difficult to deform even when heated and cooled, and excellent handling properties are likely to be achieved. In short, if the tensile modulus of the base film layer is above the lower limit value, the deformation of the buffer layer during heating and cooling in processing is effectively mitigated by the elasticity of the base film layer, preventing wrinkles from forming in the multilayer film, and thus the physical properties (such as surface smoothness) of the resulting processed product are likely to be improved. Even when the content of F polymer in the buffer layer or the thickness of the buffer layer is high, making it prone to deformation of the buffer layer, it is easy to obtain a processed product with excellent physical properties. Furthermore, if the tensile modulus of the base film layer is below the upper limit value, the flexibility of the multilayer film is likely to be further enhanced.
[0086] The imide group density of the PI included in the base film layer is preferably 0.20 to 0.35. If the imide group density is below the upper limit value, the absorption rate of the base film layer becomes lower, making it easier to suppress changes in the dielectric properties of the multilayer film. If the imide group density is above the lower limit value, the imide groups function as polar groups, which not only improves the adhesion between the base film layer and the buffer layer but also makes it easier for the absorption rate to decrease significantly.
[0087] In addition, if the above imide group density is within this range, it is easy for wrinkles to form during the processing of the multilayer film.
[0088] In addition, the imide group density is the value obtained by dividing the molecular weight per unit of the imide group portion (140.1) by the molecular weight per unit of the polyimide in the polyimide in which the polyimide precursor is imidized. For example, the imide group density of the polyimide (molecular weight per unit: 382.2) obtained by imidizing a polyimide precursor consisting of 1 mole of pyromellitic acid dihydride (molecular weight: 218.1) and 1 mole of 3,4'-oxydianiline (molecular weight: 200.2) is 0.37, which is the value obtained by dividing 140.1 by 382.2.
[0089] In the multilayer film of the present invention, it is preferable that the base film layer and each buffer layer are in direct contact. In this case, the multilayer film is likely to have excellent heat resistance and water resistance. In addition, the occurrence of warping of the multilayer film is likely to be suppressed.
[0090] In a multilayer film, the thickness of the buffer layer is more preferably 5 μm or more, and more preferably 10 μm or more. The thickness of the buffer layer is preferably 200 μm or less, and more preferably 100 μm or less. The thickness of each buffer layer is preferably the same.
[0091] In the multilayer film, the thickness of the base film layer is preferably 10 μm or more, and more preferably 25 μm or more. The thickness of the buffer layer is preferably 100 μm or less, and more preferably 50 μm or less. In this case, the multilayer film is likely to have excellent heat resistance and low linear expansion properties.
[0092] The ratio of the total thickness of the buffer layer to the thickness of the base film layer is preferably 0.8 or higher, and more preferably 1.0 or higher. The ratio of the total thickness is preferably 10 or lower, and more preferably 5 or lower.
[0093] When the thickness of the base film layer is 50 μm or less, the thickness of each buffer layer is preferably 5 μm or more, and more preferably 10 μm or more. In this case, the multilayer film is likely to have excellent heat resistance.
[0094] The thickness of the multilayer film is preferably 50 μm or more, and more preferably 75 μm or more. The thickness of the multilayer film is preferably 300 μm or less, and more preferably 150 μm or less.
[0095] In this case, the multilayer film is likely to have excellent heat resistance and low linear expansion.
[0096] The thermal expansion rate of the multilayer film is preferably -2 to +1%, and more preferably -1.5 to 0%. When processed into a printed circuit board, such a multilayer film does not easily develop wrinkles and can maintain a high yield. In addition, since such a multilayer film has excellent thermal shock resistance, when processed into a printed circuit board, it has high thermal shock resistance when forming through-holes or vias, and as a result, it is easy to obtain a printed circuit board that does not easily develop open circuits.
[0097] In addition, the thermal expansion rate can be calculated using the following method.
[0098] At 25°C, a straight line of approximately 10 cm in length is drawn on a multilayer film of 12 cm by 12 cm, and the distance between the ends of the straight line is set as the initial length L0. Subsequently, the multilayer film is heat-treated at 150°C for 30 minutes and cooled to 25°C. Then, the straight line distance L1 between the ends of the straight line drawn on the multilayer film is measured, and the thermal expansion rate (%) is calculated by the following formula.
[0099] Thermal expansion rate (%) = (L1 / L0-1) × 100
[0100] The surface of the multilayer film may be surface-treated with a silane coupling agent, etc., or surface-modified by corona treatment, plasma treatment, etc. Additionally, the surface of the multilayer film may be surface-roughened or annealed.
[0101] In particular, if the surface of a multilayer film is plasma-treated, it is easy to laminate with other materials. Regarding plasma treatment, atmospheric pressure plasma treatment and vacuum plasma treatment are preferred.
[0102] Examples of methods for manufacturing a multilayer film of the present invention include a method of forming each buffer layer with a liquid composition comprising a powder of an F polymer (i.e., an aggregate of particles containing an F polymer) (hereinafter also referred to as “the present method 1”), and a method of forming each buffer layer with a film comprising an F polymer (hereinafter also referred to as “F film”) (hereinafter also referred to as “the present method 2”).
[0103] The definitions and scopes of PI, base film layer, F polymer, buffer layer, and multilayer film in Article 1 of this Act are the same as the definitions of PI, base film layer, F polymer, buffer layer, and multilayer film in a multilayer film, including preferred embodiments.
[0104] The content of the F polymer in the powder of the F polymer in the present method 1 (hereinafter also referred to as "F powder") is preferably 80 mass% or more, and more preferably 100 mass%.
[0105] Other components that may be included in the particles of F powder include resins other than F polymer or inorganic fillers.
[0106] Examples of the above resins include aromatic polyester, polyamideimide, thermoplastic polyimide, polyphenylene ether, and polyphenylene oxide.
[0107] Examples of inorganic fillers include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride, and magnesium metasilicate (steatite). At least a portion of the surface of the inorganic filler may be surface-treated.
[0108] Particles of F powder containing a resin or inorganic filler other than the F polymer may have a core-cell structure in which the F polymer is the core and the resin or inorganic filler other than the F polymer is the cell, or may have a core-cell structure in which the F polymer is the cell and the resin or inorganic filler other than the F polymer is the core. Such particles of F powder are obtained, for example, by bonding (collision, aggregation, etc.) particles of the F polymer and particles of the resin or inorganic filler other than the F polymer.
[0109] The D50 of the F powder is preferably 0.1 to 6 μm, and the D90 of the F powder is preferably 10 μm or less.
[0110] In the liquid composition according to the present method 1, the content of F powder is preferably 5 to 40 mass%. In this case, due to the densely included F powder, a dense buffer layer is easily formed, and the physical properties of the F polymer in the buffer layer are easily expressed significantly.
[0111] The liquid composition in accordance with the present invention 1 preferably includes a liquid dispersion medium. The liquid dispersion medium is a liquid compound that is inert at 25°C and functions as a dispersion medium for the F powder.
[0112] The boiling point of the liquid dispersion medium is preferably 125 to 250 ℃.
[0113] As a liquid dispersion medium, one or more liquid compounds selected from the group consisting of water, amides, ketones, and esters are preferred, and N-methyl-2-pyrrolidone (NMP), γ-butyrolactone, cyclohexanone, and cyclopentanone are more preferred.
[0114] The content of the liquid dispersion medium in the liquid composition is preferably 50 to 80 mass%.
[0115] The viscosity of the liquid composition is preferably 50 to 1000 mPa·s or less, and the thixo ratio of the liquid composition is preferably 1.0 to 2.0 or less.
[0116] The liquid composition may include acetylene-based surfactants, silicone-based surfactants, fluorine-based surfactants, etc., in order to improve dispersion stability and handling properties.
[0117] The liquid composition preferably further includes an inorganic filler to further improve the low linear expansion and electrical properties of the buffer layer. The definition and scope of the inorganic filler are the same as the definition and scope of the inorganic filler in a multilayer film, including preferred embodiments.
[0118] The liquid composition may additionally include other resins (polymers). The definition and scope of other resins, including preferred embodiments, are the same as the definition and scope of other resins in multilayer films.
[0119] The above-mentioned additives, such as surfactants or inorganic fillers, may be added to the liquid composition containing F powder, or they may be mixed with F powder in advance to form a mixture, and the mixture dispersed in a liquid dispersion medium. Alternatively, the above-mentioned surfactants or inorganic fillers may be dispersed or dissolved in a liquid dispersion medium in advance and mixed with the liquid composition containing F powder or F powder.
[0120] A specific embodiment of the present invention 1 may be an embodiment in which a liquid composition is applied to one side of a base film layer and heated to remove the liquid dispersion medium, a liquid composition is applied to the other side of a base film layer and heated to remove the liquid dispersion medium, and further heated to calcin the F polymer to form respective buffer layers to obtain a multilayer film.
[0121] The temperature for heating the former is preferably 120 to 200 ℃. The temperature for heating the latter is preferably a temperature higher than the melting temperature of the F polymer, specifically 280 to 400 ℃ is preferred, and 300 to 380 ℃ is more preferred.
[0122] The latter heating time is preferably 30 seconds to 5 minutes, and more preferably 1 to 2 minutes.
[0123] Each heating method includes using an oven, using a ventilation drying oven, and irradiating with heat rays such as infrared rays.
[0124] The atmosphere during heating may be under either atmospheric pressure or reduced pressure. Additionally, the atmosphere may be any of an oxidizing gas atmosphere (such as oxygen gas), a reducing gas atmosphere (such as hydrogen gas), or an inert gas atmosphere (such as noble gas or nitrogen gas).
[0125] The application of the liquid composition to the base film layer can be carried out by coating methods such as spray method, roll coat method, spin coat method, gravure coat method, micro-gravure coat method, gravure offset method, knife coat method, kiss coat method, bar coat method, die coat method, Fountain Mayer bar method, slot die coat method, etc.
[0126] The definitions and scopes of PI, base film layer, F polymer, buffer layer, and multilayer film in Article 2 of this Act are the same as the definitions and scopes of PI, base film layer, F polymer, buffer layer, and multilayer film in a multilayer film, including preferred embodiments.
[0127] In the present invention 2, the thickness of the F film is preferably 5 μm or more, and more preferably 10 μm or more. The thickness of the F film is preferably 200 μm or less, and more preferably 100 μm or less.
[0128] The content of F polymer in the F film is preferably 50 mass% or more, and more preferably 60 mass% or more. The upper limit of the F polymer content is 100 mass%.
[0129] The F film may additionally include other resins (polymers), inorganic fillers, and additives. The definitions and scopes of other resins, inorganic fillers, and additives are the same as those of other resins, inorganic fillers, and additives in multilayer films, including preferred embodiments.
[0130] A specific embodiment of the present invention 2 may be an embodiment in which a base film layer is formed by compressing two F films and then heat-pressing them to bond them together to obtain a multilayer film.
[0131] The press temperature in the heat press is preferably 310 to 400 ℃.
[0132] It is preferable to perform the heat press at a vacuum of 20 kPa or less to suppress the incorporation of air bubbles.
[0133] In addition, when heat pressing, it is preferable to raise the temperature after reaching the aforementioned vacuum level. If the temperature is raised before reaching the vacuum level, the buffer layer is compressed while in a softened state—that is, while maintaining a certain degree of fluidity and adhesion—which may cause air bubbles.
[0134] The pressure in the heat press is preferably 0.2 to 10 MPa in terms of firmly adhering the buffer layer and the base film layer.
[0135] In particular, if the tensile modulus of the base film is greater than or equal to the lower limit described above, it is easy to suppress the occurrence of wrinkles caused by heating and cooling in the heat press.
[0136] The metal-coated laminate of the present invention comprises a base film layer comprising PI, a buffer layer comprising an F polymer formed on both sides of the base film layer, and a metal foil layer formed on the surface of at least one of the buffer layers (the side opposite to the base film layer).
[0137] Metals constituting the metal foil layer include copper, copper alloy, stainless steel, nickel, nickel alloy (including 42 alloy), aluminum, aluminum alloy, titanium, and titanium alloy.
[0138] As the metal foil for forming the metal foil layer, copper foil is preferred, rolled copper foil without distinction between front and back sides and electrolytic copper foil with distinction between front and back sides are more preferred, and rolled copper foil is even more preferred. Since rolled copper foil has low surface roughness, transmission loss can be reduced even when the metal-clad laminate is processed into a printed circuit board. In addition, it is preferable to use rolled copper foil after removing rolling oil by immersing it in a hydrocarbon-based organic solvent.
[0139] The 10-point average roughness of the surface of the metal foil layer is preferably 0.01 to 4 μm. In this case, adhesion with the buffer layer is improved, making it easier to obtain a printed circuit board with excellent transmission characteristics.
[0140] The surface of the metal foil layer may be treated with a glazing process. Methods of glazing include forming a glazing treatment layer, dry etching, and wet etching.
[0141] The thickness of the metal foil layer is preferably less than 20 μm, and more preferably 2 to 15 μm.
[0142] In addition, the surface of the metal foil layer may be treated with a silane coupling agent in part or in whole.
[0143] A method for manufacturing a metal-coated laminate involves overlapping a multilayer film and a metal foil so that the buffer layer of the multilayer film and the metal foil come into contact, and then laminating them by heat pressing. Since the multilayer film has excellent high-temperature heat resistance, bending and wrinkling do not easily occur when laminated with the metal foil.
[0144] At this time, the surface of the F film may be surface-treated to improve the low linear expansion and peel strength of the metal-clad laminate.
[0145] The metal-clad laminate of the present invention has excellent various physical properties, such as electrical properties, heat resistance including solder reflow resistance, drillability, chemical resistance, and surface smoothness. For this reason, the metal-clad laminate of the present invention is desirable as a printed circuit board material and can be easily and efficiently processed into a flexible printed circuit board or a rigid printed circuit board.
[0146] A printed circuit board is obtained by processing a metal foil layer of a metal-clad laminate of the present invention by etching to form a transmission circuit. That is, the method for manufacturing a printed circuit board of the present invention is a method of obtaining a printed circuit board by processing a metal foil of a metal-clad laminate by etching to form a transmission circuit. In addition, both wet etching and dry etching methods can be used for etching.
[0147] The metal-coated laminate of the present invention is equipped with the multilayer film of the present invention, and does not deform easily even when etched, and does not bend easily.
[0148] In the manufacture of a printed circuit board, after forming a transmission circuit, an interlayer insulating film may be formed on the transmission circuit, and a conductor circuit may be additionally formed on the interlayer insulating film. The interlayer insulating film may be formed using the liquid composition described above.
[0149] The solder heat resistance temperature of the metal-clad laminate of the present invention is preferably 288°C or higher, more preferably 300°C or higher, and even more preferably 320°C or higher. The solder heat resistance temperature is preferably 380°C or lower. The metal-clad laminate of the present invention is equipped with the multilayer film of the present invention, and since it exhibits excellent high-temperature heat resistance due to the mechanism of action described above, it is easy to achieve a solder heat resistance temperature within this range.
[0150] By using the metal-clad laminate of the present invention, the occurrence of swelling, warping, and peeling of the multilayer film, which is an electrical insulating layer, is suppressed during the solder reflow process (a process of heating a solder paste applied to a printed circuit board material), which is a high-temperature process in the mounting process of a printed circuit board, thereby enabling the production of a printed circuit board with production efficiency.
[0151] In addition, the solder heat resistance temperature is measured by the following method.
[0152] A metal foil layer of a metal-clad laminate with sides of 4 cm is patterned into a square of sides of 2.5 cm and floated in a solder bath at an initial temperature of 250 ℃ to observe for any external abnormalities (external defects such as expansion, bubbles, or layer separation).
[0153] If there are no abnormalities in the appearance, the temperature of the solder bath is raised, and the presence or absence of external abnormalities is observed in the same manner. The temperature of the solder layer is raised and observed repeatedly, and the highest temperature at which no abnormalities occur is set as the solder heat resistance temperature.
[0154] In the present invention, even when the printed circuit board is subjected to a solder reflow process (a process of applying solder paste to the printed circuit board material and heating it), which is a high-temperature process in the mounting process of manufacturing the printed circuit board, swelling at the interface between the base film layer and the buffer layer or warping of the printed circuit board does not easily occur.
[0155] Examples
[0156] 1. Preparation of each component and each part
[0157] [F Polymer]
[0158] F Polymer 1: PFA-based polymer containing TFE units, NAH units, and PPVE units in this order, 98.0 mol%, 0.1 mol%, and 1.9 mol% (melting temperature: 300 ℃)
[0159] F Polymer 2: PFA-based polymer containing 97.5 mol% and 2.5 mol% of TFE units and PPVE units, respectively (melting temperature: 305 ℃)
[0160] Non-F polymer 1: FEP-based polymer containing TFE units, ethylene units, hexafluoropropene units, and perfluoro(1,1,5-trihydro-1-pentene) units in this order, 40.8 mol%, 44.8 mol%, 13.9 mol%, and 0.5 mol% (melting temperature: 162 ℃)
[0161] In addition, F polymer 1 contains carbonyl groups, with a main chain having 1 × 10 carbon atoms. 6 Each has 1000 pieces, and F polymer 2 has 40 pieces.
[0162] [Powder]
[0163] Powder composed of Powder 1 : F Polymer 1, with a D50 of 2.1 μm
[0164] Powder 2 : Powder with a D50 of 1.8 μm composed of F polymer 2
[0165] Powder 3: Powder consisting of non-F polymer 1, with a D50 of 2.2 μm
[0166] [Surfactant]
[0167] Surfactant 1 : CH2=C(CH3)C(O)OCH2CH2(CF2)6F and CH2=C(CH3)C(O)(OCH2CH2) 23 A nonionic polymer that is an OH copolymer and has a fluorine content of 35 mass%
[0168] [Weapon Filler]
[0169] Filler 1: Silica filler with a D50 of 0.4 µm
[0170] [Varnish]
[0171] Varnish 1: Varnish in which thermoplastic aromatic polyimide (PI1) is dissolved in NMP (solids concentration: 18 mass%)
[0172] [Liquid dispersion medium]
[0173] NMP: N-methyl-2-pyrrolidone
[0174] [Base Film]
[0175] Polyimide film 1: An aromatic polyimide film having a thickness of 50 μm, a glass transition point of 245 °C, and a tensile modulus of 0.3 GPa at 320 °C.
[0176] Polyimide film 2: An aromatic polyimide film having a thickness of 50 μm, a glass transition point of 330 °C, and a tensile modulus of 0.2 GPa at 320 °C.
[0177] [Copper foil]
[0178] Copper foil 1: Electrolytic copper foil with a thickness of 18 µm
[0179] 2. Example of preparation of dispersion (liquid composition)
[0180] First, powder 1, varnish 1, surfactant 1, and NMP were added to a pot, and zirconia balls were added. Then, the pot was rolled at 150 rpm for 1 hour to prepare the composition.
[0181] In another port, filler 1, surfactant 1, and water were added, and zirconia balls were added. Then, the port was rolled at 150 rpm for 1 hour to prepare the composition.
[0182] In another port, the composition of both was introduced, and zirconia balls were introduced. Then, the port was rolled at 150 rpm for 1 hour to obtain dispersion 1 (viscosity: 400 mPa·s) containing powder 1 (14 parts by mass), filler 1 (7 parts by mass), PI1 (1 part by mass), surfactant 1 (3 parts by mass) and NMP (75 parts by mass).
[0183] Dispersions 2 to 5 were obtained by making them identical to dispersion 1, except that the types and amounts of powder, inorganic filler, and aromatic polyimide (PI1) were changed as shown in Table 1 below.
[0184]
[0185] 3. Example of manufacturing a multilayer film
[0186] A dispersion 1 was applied to one side of polyimide film 1 using a small-diameter gravure reverse method and passed through a ventilation drying oven (oven temperature 150°C) for 3 minutes to remove NMP and form a dried film. In addition, a dispersion 1 was applied to the other side of polyimide film 1 in the same manner and dried to form a dried film.
[0187] Next, the polyimide film 1, having a dry film formed on both sides, was passed through a far-infrared furnace (furnace temperature of 300°C near the inlet and outlet, furnace temperature of 340°C near the center) for 20 minutes to melt and sinter powder 1.
[0188] Thus, by forming a buffer layer (thickness: 25 μm) containing F polymer 1 on both sides of polyimide film 1, a film (multilayer film 1) was obtained in which the buffer layer, the polyimide film layer, and the buffer layer were directly formed in this order.
[0189] Multilayer films 2 to 5 were obtained by making them identical to multilayer film 1, except that dispersion 1 was changed to dispersions 2 to 5, respectively.
[0190] Multilayer film 6 was obtained by making it identical to multilayer film 1, except that the thickness of the buffer layer was changed to 12 μm.
[0191] In addition, a multilayer film 7 was obtained by making it identical to multilayer film 1, except that dispersion 1 was changed to dispersion 2 and polyimide film 1 was changed to polyimide film 2.
[0192] 4. Example of manufacturing a copper-clad laminate
[0193] Copper foil 1 was placed on each side of a multilayer film 1 to be in contact with a buffer layer, and a vacuum heat press (press temperature: 320 ℃, press pressure: 2 MPa, press time: 2 minutes) was performed to obtain a copper-clad laminate 1.
[0194] Copper-clad laminate 1 is a laminate in which an electrolytic copper foil layer, a buffer layer, a base film layer, a buffer layer, and an electrolytic copper foil layer are laminated in this order.
[0195] In addition, prior to vacuum heat pressing, the surface of the buffer layer of multilayer film 1 is subjected to a high-frequency voltage of 40 kHz (discharge power density: 300 W·min / m²). 2Under the conditions of ), the surface was treated by vacuum plasma treatment (vacuum degree: 20 Pa) using a mixed gas of 95 volume% argon and 5 volume% hydrogen (flow rate: 2000 sccm).
[0196] Copper-clad laminates 2 to 7 were obtained by making them identical to copper-clad laminate 1, except that multilayer film 1 was changed to multilayer films 2 to 7.
[0197] 5. Example of manufacturing a printed circuit board
[0198] The electrolytic copper foil layer of the copper-clad laminate 1 was processed by etching to form a transmission circuit, thereby obtaining a printed circuit board 1. In addition, the transmission circuit in the printed circuit board 1 was formed such that 200 patterns with a width of 100 μm and a length of 100 mm were formed.
[0199] Printed circuit boards 2 to 7 were obtained by making them identical to printed circuit board 1, except that copper-clad laminate 1 was changed to copper-clad laminates 2 to 7.
[0200] 6. Evaluation of Multilayer Films
[0201] 6-1. Evaluation of Adhesion
[0202] A rectangular test specimen with a length of 100 mm and a width of 10 mm was cut from the obtained multilayer film. Then, the base film layer and the buffer layer were peeled off from one end of the test specimen in the longitudinal direction to a position of 50 mm. Subsequently, with the position of 50 mm from one end of the test specimen in the longitudinal direction as the center, the maximum load when peeling 90 degrees at a tensile speed of 50 mm / min was used with a tensile testing machine (manufactured by Orientec Co., Ltd.) and evaluated according to the following criteria, with the maximum load being the peel strength (N / cm).
[0203] ○ : Peel strength ≥ 10 N / cm
[0204] × : Peel strength < 10 N / cm
[0205] 6-2. Evaluation of Adhesion After High Temperature and High Humidity Treatment
[0206] From the obtained multilayer film, a rectangular test specimen with a length of 100 mm and a width of 10 mm was cut, maintained for 72 hours in an atmosphere of 85°C and 85% relative humidity, and then the peel strength was measured in the same manner as in 6-1 and evaluated according to the following criteria.
[0207] ○ : Peel strength ≥ 5 N / cm
[0208] △ : 3 N / cm < peel strength < 5 N / cm
[0209] × : Peel strength ≤ 3 N / cm
[0210] 6-3. Evaluation of Thermal Stretchability
[0211] From the obtained multilayer film, a sample cut to a width and length of 12 cm was prepared, and the thermal expansion rate was calculated using the following method.
[0212] At 25 ℃, a straight line of approximately 10 cm in length is drawn on the sample, and the distance between the ends of the straight line is set as the initial length L0. Subsequently, the sample is heat-treated at 150 ℃ for 30 minutes and cooled to 25 ℃. Then, the straight line distance L1 between the ends of the straight line drawn on the sample is measured and expressed as the thermal expansion rate (%) according to the following formula.
[0213] Thermal expansion rate (%) = (L1 / L0-1) × 100
[0214] In addition, the thermal stretchability of the multilayer film was evaluated according to the following criteria.
[0215] ○ : The thermal expansion rate is -1.5% or more and 0% or less.
[0216] △ : Thermal expansion rate is -2% or more and less than -1.5%, or greater than 0% and less than or equal to 1%.
[0217] × : Thermal expansion is less than -2% or greater than 1%.
[0218] 6-4. Evaluation of Electrical Characteristics
[0219] From the obtained multilayer film, a piece of material measuring 10 cm in length and 5 cm in width was cut, and the dielectric loss tangent (measurement frequency: 10 GHz) of the multilayer film was measured using the SPDR (Split Post Dielectric Resonance) method and evaluated according to the following criteria.
[0220] ○ : The genetic apex is less than 0.0010.
[0221] △ : The genetic null tangent is 0.0010 or greater and 0.0025 or less.
[0222] × : The genetic tangent is greater than 0.0025.
[0223] 7. Evaluation of Copper-Covered Laminates
[0224] 7-1. Evaluation of Solder Float Resistance
[0225] The obtained copper-clad laminate was cut into 5 cm by 5 cm pieces, and the appearance of the copper-clad laminate after being placed in a solder bath at 288°C for 5 seconds, 5 times, was evaluated according to the following criteria.
[0226] ○ : No swelling or peeling can be observed.
[0227] △ : No swelling was observed, but delamination was seen in some areas.
[0228] × : Swelling and peeling were observed.
[0229] 7-2. Evaluation of Machinability
[0230] For the obtained copper-clad laminate, a UV-YAG laser with a wavelength of 355 nm was irradiated using a laser processing machine to create a circular shape with a diameter of 100 μm. This formed circular through holes in the copper-clad laminate.
[0231] In addition, the laser output was set to 1.2 W, the laser focal diameter to 25 μm, the number of rotations around the circumference to 20, and the oscillation frequency to 40 kHz.
[0232] After that, a fragment of the copper-clad laminate containing the through hole was cut out and hardened with a thermosetting epoxy resin. Subsequently, it was polished until the cross-section of the through hole was exposed, the cross-section of the part where the through hole was formed was observed under a microscope, the periphery of the through hole was visually inspected, and evaluated according to the following criteria.
[0233] ○ : No cutting or peeling is observed at the layer interface inside the through hole.
[0234] △ : At the layer interface inside the through hole, cutting is observed, but peeling is not observed.
[0235] × : The occurrence of cutting and peeling is confirmed at the layer interface inside the through hole.
[0236] 8. Evaluation of Printed Circuit Boards
[0237] 8-1. Evaluation of the Open Line Rate of Transmission Circuit Patterns
[0238] The resistance values of both ends of each pattern of the transmission circuit of the obtained printed circuit board were measured and evaluated according to the following criteria.
[0239] ○ : All patterns have a resistance value of 10 Ω or less (Flat line rate: 0 %).
[0240] △ : There is one pattern indicating a resistance value greater than 10 Ω (open circuit rate: 0.5 %).
[0241] × : There are two or more patterns showing a resistance value greater than 10 Ω (Flat line rate: 1% or more).
[0242] The results for each are summarized and shown in Table 2.
[0243]
[0244] Industrial applicability
[0245] According to the present invention, a multilayer film having a base film layer comprising polyimide and a buffer layer comprising a tetrafluoroethylene-based polymer formed on both sides of the base film layer, a metal-clad laminate, and a printed circuit board can be obtained.
[0246] These are all useful as printed circuit boards used for transmitting high-frequency signals, and can also be processed and used as antenna components, insulating layers for power semiconductors, aircraft parts, automotive parts, etc.
[0247] In addition, the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2020-062112 filed on March 31, 2020 are incorporated herein by reference and accepted as disclosure of the specification of the present invention.
Claims
Claim 1 A multilayer film comprising a base film layer containing a polyimide having a glass transition point of less than 288°C, and a buffer layer formed on both sides of the base film layer, wherein the buffer layer comprises a tetrafluoroethylene-based polymer having a melting temperature of 288°C or higher and a unit based on perfluoro(alkyl vinyl ether), and a buffer layer comprising an aromatic polymer which is a maleimide resin or a polyimide, wherein the content of the tetrafluoroethylene-based polymer in the buffer layer is 50 mass% or more, and the ratio of the total content of the aromatic polymer to the content of the tetrafluoroethylene-based polymer is 0.01 to 0.
5. Claim 2 A multilayer film according to claim 1, wherein the base film layer and each of the buffer layers are in direct contact. Claim 3 A multilayer film according to claim 1, wherein the thickness of the multilayer film is 50 μm or more. Claim 4 A multilayer film according to claim 1, wherein the thickness of the base film layer is 50 μm or less and the thickness of each buffer layer is 5 μm or more. Claim 5 A multilayer film according to claim 1, wherein the ratio of the total thickness of the buffer layer to the thickness of the base film layer is 0.8 or more. Claim 6 A multilayer film according to claim 1, wherein the tensile modulus of the base film layer at 320°C is 0.2 GPa or higher. Claim 7 A multilayer film according to claim 1, wherein the tetrafluoroethylene-based polymer comprises a perfluoro(alkyl vinyl ether)-based unit and is a polymer having polar functional groups, or comprises 2.0 to 5.0 mol% of the perfluoro(alkyl vinyl ether)-based unit with respect to the total units and is a polymer not having polar functional groups. Claim 8 A multilayer film according to claim 1, wherein the thermal expansion rate measured by heating the multilayer film at 150°C for 30 minutes is -2 to +1%. Claim 9 A method for manufacturing a multilayer film as described in any one of claims 1 to 8, wherein each of the buffer layers is formed from a liquid composition comprising a powder of the tetrafluoroethylene-based polymer. Claim 10 A method for manufacturing a multilayer film as described in any one of claims 1 to 8, wherein each of the buffer layers is formed as a film comprising the tetrafluoroethylene-based polymer. Claim 11 A metal-coated laminate comprising a base film layer containing a polyimide having a glass transition point of less than 288°C, a buffer layer formed on both sides of the base film layer, and a metal foil layer formed on the side of at least one of the buffer layers opposite to the base film layer, wherein the buffer layer comprises a tetrafluoroethylene-based polymer having a melting point of 288°C or higher and a unit based on perfluoro(alkyl vinyl ether), and an aromatic polymer having a maleimide resin or polyimide, wherein the content of the tetrafluoroethylene-based polymer in the buffer layer is 50 mass% or more, and the ratio of the total content of the aromatic polymer to the content of the tetrafluoroethylene-based polymer is 0.01 to 0.
5. Claim 12 In claim 11, a metal-clad laminate, which is a printed wiring board material. Claim 13 In claim 11, a metal-clad laminate having a solder heat resistance temperature of 288°C or higher. Claim 14 A method for manufacturing a printed circuit board, wherein the metal foil layer of a metal-clad laminate described in any one of claims 11 to 13 is processed by etching to form a transmission circuit, thereby obtaining a printed circuit board. Claim 15 delete
Citation Information
Patent Citations
Material for printed circuit board, metal laminate, method for manufacturing same, and method for manufacturing printed circuit board
KR1020180004710A
